Monster trucks [videorecording (DVD)] - Till, Lucas, 1990-; Levy, Jane, 1989-; Lennon, Thomas, 1970- (Paramount Pictures, 2017)
Looking for any way to get away from the life and town he was born into, Tripp, a high school senior, builds a Monster Truck from bits and pieces of scrapped cars. After an accident at a nearby oil-drilling site displaces a strange and subterranean creature with a taste and a talent for speed, Tripp may have just found the key to getting out of town and a most unlikely friend.